The Relationship Between Implementation of the Healthy Living Community Movement (Germas) Program Regarding the Health of the Elderly in the Rappang Health Center Working Area - Ratri Pramudita Hafid; Devy Febrianti; Khaeriyah Adri; Pratiwi Ramlan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: One of the main problems facing public health services is the global trend of an increasingly aging society which continues to pose major challenges for policy makers and health service providers as well as socio-economic challenges in the health sector. A number of challenges were encountered during the introduction of the GERMAS program, including a lack of awareness regarding physical exercise for the elderly and the importance of physical fitness. Health services rarely provide social education, thus contributing to the ignorance of the elderly. Objective: To find out the relationship between the implementation of the healthy living community movement (GERMAS) program on the health of the elderly in the Rappang Community Health Center Working Area, Panca Rijang District.. Method: A cross-sectional technique is employed in the descriptive-analytic study design. The sample in this study was 68 reapondents taken using purposive sampling. This study was carried out at the Rappang Community Health Center's operational space, Panca Rijang District, Sidenreng Rappang Regency. Result: From this research, the statistical results of the Chi-Square Test for the physical activity variable were obtained with a significance of 0.000 (p < 0.05), the fruit and vegetable consumption variable had a significance value of 0.025 (p < 0.05), the smoking behavior variable had a significance value of 0.000 (p < 0.05), the alcohol consumption variable has a significance value of 0.590 (p > 0.05), the periodic health check variable has a significance value of 0.000 (p < 0.05), the variable maintaining environmental cleanliness has a significance value of 0.007 (p < 0.05), and the variable m uses standard toilets with a significance value of 1.000 (p > 0.05). Conclusion: The conclusion that can be drawn is that the GERMAS indicators have a significant relationship with the health of the elderly, namely physical activity, consuming fruit and vegetables, smoking behavior, regular health checks and maintaining environmental cleanliness.